The house of "Seu Zé" - music and sexuality in school - José Carlos Teixeira Junior (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
This article discusses some issues that traverse the relationship between music and sexuality in everyday life in a public school. To do so, I intend to accomplish this thread following a path suggested by Benjamin: narrative as a college (apparently inalienable, but often the withdrawal) to exchange experiences. Assume this position is justified by the fact that the narrative consists of a significant part of the complex relationship between ethics and aesthetics. Narrating not mean to convey the pure thing in itself, as an information or report, but soak the thing in the life of the reporter in order to extract it from her again. In other words, music and sexuality discussed in the following pages are in no way absolutized (not relativized), but dipped in everyday encounters that weave the position of teacher in music. Thus, the ambivalence of a practice of playing (and hear) music at school (more specifically the songs sampled on the Beatbox called funk-whoring) emerges both the normativity of a stereotype of pornography as well as the tensions of his most different processes of subjectification . These processes complicate this same stereotype to spell out opportunities to speak with sexuality beyond its binaries.